Influence of Dietary Triacylglycerol Structure on the Accumulation of Docosahexaenoic Acid [22:6(n-3)] in Organs in a Short-Term Feeding Trial with Mildly Omega-3 Deficient Rats - Kulkarni, Amruta (John Wiley and Sons Inc, 2025)
Scope: To study the effect of positional distribution of docosahexaenoic acid (DHA) in dietary triacylglycerols (TAG) on the tissue fatty acid content and composition of mildly (n-3) deficient rats.
Methods and results: In a 5-day feeding trial, mildly (n-3) deficient rats received 360 mg daily structured TAGs: sn-22:6(n-3)-18:0-18:0, sn-18:0-18:0-22:6(n-3), sn-18:0-22:6(n-3)-18:0, or tristearin. A fifth group receives standard (n-3) adequate feed AIN-93G from birth till the end of the trial. The DHA-fed groups show significantly higher DHA levels in the liver and visceral fat compared to the tristearin or normal feed groups showing that the dose and the short feeding period of DHA were sufficient to restore the DHA content in the organs of (n-3) deficient rats. Feeding sn-1 DHA resulted in higher levels of DHA in the liver TAG compared to sn-3 DHA feeding, although the difference did not reach statistical significance.
Conclusion: These findings indicated a possible difference in the tissue accumulation and/or metabolic fate of DHA from the sn-1 and sn-3 positions of TAG.
© 2024 The Authors. Molecular Nutrition & Food Research published by Wiley-VCH GmbH.